2023
DOI: 10.1021/acs.organomet.3c00077
|View full text |Cite
|
Sign up to set email alerts
|

Putting on the Crown: Synthesis and Reactivity of Trimethyltitanium

Abstract: The trimethyltitanium complex (Me 3 TACN)TiMe 3 (Me 3 TACN = 1,4,7-Me 3 -1,4,7-triazacyclononane) is obtained by reacting (Me 3 TACN)TiCl 3 with methyllithium in the cold. The isolation of pure (Me 3 TACN)TiMe 3 was achieved via direct crystallization from the filtered reaction mixture or by extraction of the reaction residue with toluene. A similar reaction with neosilyllithium comes to a halt at the bis(alkyl) complex (Me 3 TACN)TiCl(CH 2 SiMe 3 ) 2 . Treatment of (Me 3 TACN)TiMe 3 with ClSiMe 3 or TfOSiMe 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 73 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…Protonolysis of the YÀ CH 3 moieties under methane elimination seemed the most immediate transformation to study, [22] since the reaction of [(Me 3 TACN)ScMe 3 ] with methanol has been shown to afford [(Me 3 TACN)Sc(OMe) 3 ] in decent yield. [17] Probing both a considerably less Brønsted acidic and sterically more demanding proligand, we examined silylamine HN(SiHMe 2 ) 2 . The latter has been previously successfully applied to convert amorphous unsolvated [YMe 3 ] n into homoleptic silylamide [Y {N(SiHMe 2 ) 2 } 3 ] 2 .…”
Section: Reactions Of [(Me 3 Tacn)yme 3 ] With Tetramethyldisilazane ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Protonolysis of the YÀ CH 3 moieties under methane elimination seemed the most immediate transformation to study, [22] since the reaction of [(Me 3 TACN)ScMe 3 ] with methanol has been shown to afford [(Me 3 TACN)Sc(OMe) 3 ] in decent yield. [17] Probing both a considerably less Brønsted acidic and sterically more demanding proligand, we examined silylamine HN(SiHMe 2 ) 2 . The latter has been previously successfully applied to convert amorphous unsolvated [YMe 3 ] n into homoleptic silylamide [Y {N(SiHMe 2 ) 2 } 3 ] 2 .…”
Section: Reactions Of [(Me 3 Tacn)yme 3 ] With Tetramethyldisilazane ...mentioning
confidence: 99%
“…More recently, the crystal structures of [(Me 3 TACN)LnMe 3 ] (Ln=Sc, Y, Yb, Lu) have been elucidated [14–16] . Previous reactivity studies also include the redox transformation of the ytterbium congener in the presence of AlMe 3 and GaMe 3 , [16] the controlled ClSiMe 3 ‐promoted Me/Cl exchange at the yttrium center, [15] as well as the exhaustive protonolysis of the scandium congener with methanol [17] . It was also revealed that the 89 Y nucleus ( I = 1/2 ${{ 1/2 }}$ , natural abundance=100 %) [18] is a useful complementing probe for assessing the alkylation degree/substitution pattern at the rare‐earth‐metal center and any involved decomposition reactions, via heteronuclear NMR spectroscopy [15,19–21] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation